Evaluation of occupational health practice in the laundry and linen service at Kenyatta National hospital, Nairobi City County, Kenya - Jebet, Sharon J.; Warutere, Peterson N.; Mugo, Judy M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Health facility laundry ensures provision of enough, dirt free and continuous provision of garments for medical use. Main activities involve: Arranging, thorough cleaning, disinfecting, packing and dispatch. Safety hazards are features in the workplace with a potential to cause harm. This study aimed at evaluating occupational health practise of laundry and linen services at Kenyatta National hospital in the Nairobi City County, Kenya. Specifically, the study sought to ascertain potential hazards, determine adherence levels and establish wet bulb globe temperature of workers in the Laundry and Linen Service at Kenyatta National Hospital. Methods: This research adopted a cross-sectional analytical design through a questionnaire that was structured. One-forty (140) participants were recruited for interviewing through a systematic random sampling technique. Data was cleaned and analysis was done by use of version 22.0 of SPSS software. A Chi-test was calculated to show associations between variables. Results: The analysis of association revealed that age (χ2(2)=9.091, p=0.011, p<0.05), level of education attained (χ2(1)=10.76, p=0.001, p<0.05) and marital status (χ2(2)=9.768, p=0.008, p<0.05) were had a signification association with knowledge on environmental aspects in laundry and linen services. Conclusions: The hospital has made significant efforts in implementing various health and safety programs which can be adopted across different departments. The hospital management needs to ensure that workers are continuously trained on existing and emerging safety hazards, implementation of safety protocols and installation of AC system and improved ventilation within the laundry.